Congenital complete heart block in the setting of severe pre-eclampsia requiring urgent cesarean section. (November 2020) - Preston, D.; Klucsarits, S.; Moon, T.; Nasir, D.
Highlights: Congenital complete heart block presents significant risks during pregnancy. Pre-eclampsia may complicate hemodynamic changes in complete heart block. Anesthesia for those with complete heart block requires aggressive planning. Abstract: Congenital complete heart block is a rare phenomenon that may be discovered during pregnancy in patients who were previously asymptomatic. Peripartum management of these patients mandates a multidisciplinary approach with careful planning regarding indications for pacing, appropriate anesthetic technique, and contingency planning. Approaches to anesthetic management for congenital complete heart block have been described, but management in association with severe pre-eclampsia has not been reported. We describe the anesthetic management of a parturient with complete heart block who presented with severe pre-eclampsia requiring urgent cesarean section.